Metode Pembiasaan Sholat sebagai Upaya Penanaman Nilai Religiusitas Anak Usia Dini - Sarwini Sarwini; Ning Yuliyanti; Siti Jannah; Maharani Maharani (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2025)
Instilling religious values in early childhood is an important foundation for developing Islamic character. One effective approach is through the practice of prayer. This study aims to describe the application of the practice of prayer in the daily activities of early childhood and its impact on the development of children's religiosity. The research method used was descriptive qualitative, using observation, interviews, and documentation techniques with Kindergarten B students at BA Aisyiyah Paseban II. The results indicate that consistent practice of prayer, such as congregational Dhuha prayer and prayer before studying, can foster spiritual awareness, love for God, and discipline in children. This method also reinforces Islamic values in a natural and enjoyable way. Thus, the practice of prayer is an effective strategy for developing children's religiosity from an early age. Keywords: religiosity, early childhood, habituation of prayer, Islamic education